2014
DOI: 10.1007/s00712-014-0407-3
|View full text |Cite
|
Sign up to set email alerts
|

Privatization in the presence of foreign competition and strategic policies

Abstract: Abstract:Recent evidence shows that developing and transition economies are increasingly privatizing their public …rms and also experiencing rapid growth of inward foreign direct investment (FDI). In an international mixed oligopoly with strategic tax/subsidy policies, we analyze the interaction between privatization and FDI. We …nd that the incentive for FDI increases with privatization. However, the possibility of FDI reduces the degree of privatization. Our paper shows that FDI policies reducing the …xed-co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 26 publications
3
2
0
Order By: Relevance
“…Hence, there is a trade-off between consumer surplus and domestic profits. The trade-off is responsible for creating partial privatization in our analysis under FDI, which is in line with the results of Mukherjee and Suetrong (2009) and Dijkstra et al (2015).…”
Section: Welfare Analysissupporting
confidence: 89%
See 3 more Smart Citations
“…Hence, there is a trade-off between consumer surplus and domestic profits. The trade-off is responsible for creating partial privatization in our analysis under FDI, which is in line with the results of Mukherjee and Suetrong (2009) and Dijkstra et al (2015).…”
Section: Welfare Analysissupporting
confidence: 89%
“…However, greater output benefits the foreign firm more under FDI than export, because the foreign firm’s fixed cost under FDI does not depend on the output, and the transportation cost under export increases with the output of the foreign firm. Similar results were obtained by Mukherjee and Suetrong (2009) and Dijkstra et al (2015).…”
Section: Fdi or Export With Governancesupporting
confidence: 89%
See 2 more Smart Citations
“…The study found evidence that further economic growth depends on further privatization and FDI. Bouwe R. Dijkstra, Anuj Joshua Mathew, and Mukherjee (2015) analyzed the interaction between privatization and FDI and found that privatization by the domestic country increases a foreign firm's incentive for FDI.…”
Section: Some Recent Empirical Studies Of the Fdi And Privatization Rmentioning
confidence: 99%